The Influence Of Social Comparison In Social Media On Self-Esteem In Early Adulthood - Hasugian, Peronika Br; Brahmana, Karina M. (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine the influence of social comparison on social media on self-esteem in early adulthood. Based on the results of research on the influence of social comparison on social media on Self Esteem in early adulthood in Medan City, the following conclusions can be drawn: The results of the study indicate that social comparison on social media has a significant and negative effect on self-esteem in early adulthood individuals. This means that the more often someone compares themselves to others on social media, the greater the likelihood of their self-esteem or self-esteem decreasing. Most respondents in this study had a high level of self-esteem, even though they also had a high level of social comparison. This shows that not all social comparisons have a direct negative impact, because some individuals are still able to maintain a positive view of themselves, perhaps due to other factors such as social support, personality, or strong internal values. When viewed based on the social comparison aspect, it is known that physical attractiveness and lifestyle are the two aspects that are most often compared by respondents when they use social media. This means that many respondents feel triggered to compare their appearance and lifestyle with what is seen in other people's posts. While aspects of personality and wealth are also compared, but not as much as these two aspects.